Pengaruh Promosi Dan Harga Terhadap Keputusan Pembelian Pada Altic Houseware Medan - Lilis Karniah Gulo; Mery Lani Purba; Tohonan Silalahi (Universitas Sari Mutiara Indonesia, 2024)
This research is a causal associative study aimed at examining how promotion and price influence purchasing decisions at Altic Houseware Medan. The research was conducted by distributing questionnaires to 100 respondents, who were visitors to Altic Houseware Medan, using a non-probability sampling method with an accidental sampling approach. The data analysis technique used is Multiple Linear Regression Analysis. The results of this study indicate that promotion has a positive and significant effect on purchasing decisions, and price also has a positive and significant effect on purchasing decisions. The F-test results show that promotion and price simultaneously influence purchasing decisions. The coefficient of determination (R-square) is 0.659, which means that 65.9% of purchasing decisions are determined by promotion and price, while the remaining 34.1% is influenced by other variables such as service quality and others.